14. The CIX Archives: Revalorizations and Hidden Treasures - Cyrille Delhaye (Meta-Xenakis: New Perspectives on Iannis Xenakis’s Life, Work, and Legacies, 2024)
The work conducted around the conservation and valorization of the CIX archives since 2010 shows that the main collection includes all the archival documents of the association Les Ateliers UPIC. This association, founded by Iannis Xenakis in 1985, promoted the machine for aiding composition through drawing, invented at the CEMAMu in 1977, through a whole series of pedagogical actions, including composition workshops and concerts throughout the world. Among the traces left by the circa 130 composers who came to Paris to compose on UPIC, a folder constituted by Iannis Xenakis for Taurhiphanie catches one’s attention: it regroups compositional materials, UPIC pages, contextual archives, photographs of the premiere, etc. These documents highlight some aspects of the genesis of this polymorphic work, created in Arles (France) in 1987 for real-time UPIC, a percussion ensemble, horses, and bulls. After presenting the state of the art of the work in progress for the conservation and valorization of the CIX collections since 2010, this chapter dives into the depths of the collection by analyzing and contextualizing the traces left by Xenakis when he composed Taurhiphanie.